On the relationship between glucose absorption and glucose‐stimulated secretion of GLP‐1, neurotensin, and PYY from different intestinal segments in the rat. Issue 23 (4th December 2017) - Kuhre, Rune E.; Christiansen, Charlotte B.; Saltiel, Monika Y.; Wewer Albrechtsen, Nicolai J.; Holst, Jens J.
Abstract: Ingested glucose powerfully stimulates the secretion of appetite‐ and metabolism‐regulating peptide hormones from the gut – including glucagon‐like peptide‐1 (GLP‐1), neurotensin (NT), and polypeptide YY (PYY). However, the regional origin of these secretions after glucose stimulation is not well characterized, and it remains uncertain how their secretion is related to glucose absorption. We isolated and perfused either the upper (USI) or the lower (LSI) small intestine or the colon from rats and investigated concomitant glucose absorption and secretory profiles of GLP‐1, NT, and PYY. In the USI and LSI luminal glucose (20%, w/v) increased GLP‐1 and NT secretion five to eightfold compared to basal secretion. Compared to the USI, basal and stimulated GLP‐1 secretion from the colon was 8–10 times lower and no NT secretion was detected. Luminal glucose stimulated secretion of PYY four to fivefold from the LSI and from the USI and colon, but the responses in the USI and colon were 5‐ to 15‐fold lower than in the LSI. Glucose was absorbed to a comparable extent in the USI and LSI by mechanisms that partly depended on both SGLT1 and GLUT2 activity, whereas the absorption in the colon was 80–90% lower. The absorption rates were, however, similar when adjusted for segmental length. Glucose absorption rates and NT, PYY and in particular GLP‐1 secretion were strongly correlated ( P  < 0.05). Our results indicate that the rate of secretion of GLP‐1, NT, and PYY in response to glucose, regardless of the involved molecular machinery, is predominantly regulated by the rate of glucose absorption. Abstract : Little is known about the relationship between intestinal glucose absoprtion and glucose‐stimulated secretion of the gut hormones glucagon‐like peptide‐1 (GLP‐1), neurotensin (NT), and peptide yy (PYY). We directly investigated this by isolating and perfusing different parts of the rat intestine – either the upper or lower half of the small intestine or the colon. Glucose absorption rate directly correlated with the secretion of in particular GLP‐1, but also NT and PYY in the upper and lower small intestine and the colon.